2020
DOI: 10.1007/s11239-020-02103-w
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of platelet–fibrin clot strength on occurrence and clinical outcomes of peripheral artery disease in patients with significant coronary artery disease

Abstract: Patients with peripheral artery disease (PAD) have shown the increased risk of cardiovascular (CV) morbidity and mortality. This study sought to evaluate the impact of clot strength on prevalence and major adverse CV events (MACE) of PAD in high-risk patients. We enrolled patients undergoing percutaneous coronary intervention (PCI) (n = 1667) with available platelet-fibrin clot strength [thrombin-induced maximal amplitude (MA thrombin) measured by thromboelastography] and inflammation [high sensitivity C-react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…43,44 In addition, patients with polyvascular disease (e.g., CAD þ peripheral artery disease [PAD]) had a greater level of platelet-fibrin clot strength than subjects with single vascular disease. 45 Clinical trials with adjunctive DOACs have shown clinical benefit in reducing the risk of ischemic events in high-risk ASCVD patients (e.g., multivessel CAD, PAD, heart failure, diabetes mellitus, chronic kidney disease, and recurrent MI). 43,44,46 In the COMPASS (Rivaroxaban for the Prevention of Major Cardiovascular Events in Coronary or Peripheral Artery Disease) trial including stable ASCVD patients (n ¼ 27,395), 46 the vascular-dose rivaroxaban (2.5 mg twice daily) þ aspirin strategy reduced the risk of ischemic events (4.1 vs. 5.4%; HR: 0.76: 95% CI: 0.66-0.86, p < 0.001) at the expense of increased risk of major bleeding (3.1 vs. 1.9%; HR: 1.70: 95% CI: 1.40-2.05, p < 0.001) compared with aspirin monotherapy.…”
Section: Use Of Oral Anticoagulants In East Asiansmentioning
confidence: 99%
“…43,44 In addition, patients with polyvascular disease (e.g., CAD þ peripheral artery disease [PAD]) had a greater level of platelet-fibrin clot strength than subjects with single vascular disease. 45 Clinical trials with adjunctive DOACs have shown clinical benefit in reducing the risk of ischemic events in high-risk ASCVD patients (e.g., multivessel CAD, PAD, heart failure, diabetes mellitus, chronic kidney disease, and recurrent MI). 43,44,46 In the COMPASS (Rivaroxaban for the Prevention of Major Cardiovascular Events in Coronary or Peripheral Artery Disease) trial including stable ASCVD patients (n ¼ 27,395), 46 the vascular-dose rivaroxaban (2.5 mg twice daily) þ aspirin strategy reduced the risk of ischemic events (4.1 vs. 5.4%; HR: 0.76: 95% CI: 0.66-0.86, p < 0.001) at the expense of increased risk of major bleeding (3.1 vs. 1.9%; HR: 1.70: 95% CI: 1.40-2.05, p < 0.001) compared with aspirin monotherapy.…”
Section: Use Of Oral Anticoagulants In East Asiansmentioning
confidence: 99%
“…In PCI-treated patients (n=1,667), the presence of peripheral artery disease (PAD) was significantly related with elevated levels of C-reactive protein and PFCS. 5) Furthermore, high PFCS was significantly associated with worse clinical outcomes only in PAD patients. 5) …”
mentioning
confidence: 98%
“… 5) Furthermore, high PFCS was significantly associated with worse clinical outcomes only in PAD patients. 5) …”
mentioning
confidence: 98%
See 2 more Smart Citations